Epidemiology of Oestrus ovis (Diptera: Oestridae) in sheep at the Santa Catarina State Plateau, Brazil Epidemiologia de Oestrus ovis (Diptera: Oestridae) em ovinos no Planalto Catarinense - Ramos C.I. (2006)
An experiment has been carried out in the Santa Catarina Plateau to recommend a proposal for a strategy of Oestrus ovis, infestation in sheep. The prevalence, intensity and seasonal variation of O. ovis larvae in three farms of Lages, São Joaquim, and Campos Novos municipalities in the Santa Catarina State, Brazil, were assessed from october 1997 to september 2001. Three tracer lambs per property were used monthly. They had been previously housed for 30 days and suppressively treated with different active ingredients and taken to their respective farms, where they grazed for 28 days and housed again for another 20 days. After this period, they were sacrificed to collected O. ovis larvae from paranasal sinus. No infested animals with larvae of O. ovis were observed at monthly average temperatures inferior to 9.8°C. Heavier infestations occurred in spring and summer, mainly in Lages and in Campos Novos. These results suggest that strategic treatment should be done in the beginning of spring and in the end of summer.